1998
DOI: 10.1073/pnas.95.22.13159
|View full text |Cite
|
Sign up to set email alerts
|

Adenoviral-mediated gene transfer in lymphocytes

Abstract: Although adenovirus can infect a wide range of cell types, lymphocytes are not generally susceptible to adenovirus infection, in part because of the absence of the expression of the cellular receptor for the adenoviral fiber

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
123
0
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 124 publications
(130 citation statements)
references
References 40 publications
6
123
0
1
Order By: Relevance
“…One mechanism of cellular resistance to adenoviral infection appears to be mediated by lack of the fiber-dependent pathway. We have confirmed along with others 41,42 that cell lines which express a paucity of the high affinity Ad binding site, CAR, demonstrate poor susceptibility to adenoviral infection. This barrier to adenoviral binding/entry appears to be overcome in the presence of polycations like protamine.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…One mechanism of cellular resistance to adenoviral infection appears to be mediated by lack of the fiber-dependent pathway. We have confirmed along with others 41,42 that cell lines which express a paucity of the high affinity Ad binding site, CAR, demonstrate poor susceptibility to adenoviral infection. This barrier to adenoviral binding/entry appears to be overcome in the presence of polycations like protamine.…”
Section: Discussionsupporting
confidence: 83%
“…40 Likewise, CAR-transfected murine lymphocytes (normally CAR-deficient and resistant to Ad infection) were rendered more susceptible to adenoviral transduction via the same fiber-dependent pathway. 41 Although adenovirus internalization (as opposed to binding) is mediated by the interaction between adenovirus penton base and cell surface receptors, namely, alpha-v-integrin receptors (␣ v integrins), 29,30 expression of ␣ v integrin alone is not sufficient to achieve an efficient gene transfer. The expression of both receptors appears to be necessary for efficient adenoviral gene transfer.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Hidaka et al 22 reported an increase of AdV uptake by several orders of magnitude using CAR vector pretreatment in poorly permissive human dermal fibroblasts. The different results obtained could be due to the fact, that beside the absolute levels of CAR and ␣ v ␤ 3 and ␣ v ␤ 5 integrin expression 10,12,15,17,45 appropriate co-localization of CAR and ␣ v -integrins 46,47 and their expression at cellular surfaces accessible to the vector is required for efficient gene transfer. Despite strong CAR overexpression in the investigated cell lines, not all of these conditions may have been adequately fulfilled, explaining the only moderate improvement of the gene transfer rate in the present study.…”
Section: ) and High-permissive (Bon) Cells (Up To 492-fold)mentioning
confidence: 99%
“…9 Following attachment, the adenovirus uptake proceeds via ␣ v ␤ 3 and ␣ v ␤ 5 integrins which bind the penton base of the virus capsid and mediate internalization via coated pits. 10,11 Investigation of ways to overcome the resistance to adenovirus infection observed in certain nonpermissive cells, by overexpression of ␣ v -integrins 10 or CAR 1,[12][13][14] revealed, that both CAR and ␣ v -integrins are essential for virus uptake. Cancer cells show extremely variable vector uptake.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation